2020
DOI: 10.1001/jamaoncol.2019.4097
|View full text |Cite
|
Sign up to set email alerts
|

Overall Survival in Men With Bone Metastases From Castration-Resistant Prostate Cancer Treated With Bone-Targeting Radioisotopes

Abstract: for the MORPHEP Collaborative Group IMPORTANCE Both α-emitting and β-emitting bone-targeted radioisotopes (RIs) have been developed to treat men with metastatic castration-resistant prostate cancer (CRPC). Only 1 phase 3 randomized clinical trial has demonstrated an overall survival (OS) benefit from an α-emitting RI, radium 223 ( 223 Ra), vs standard of care. Yet no head-to-head comparison has been done between α-emitting and β-emitting RIs.OBJECTIVE To assess OS in men with bone metastases from CRPC treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 36 publications
1
19
0
1
Order By: Relevance
“…A more recent meta-analysis has failed to show any survival benefit from the use of beta-emitting radionuclides such as Sr-89 and Sm-153 in hormone-resistant and chemotherapy-refractory metastatic prostate cancer. [ 8 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…A more recent meta-analysis has failed to show any survival benefit from the use of beta-emitting radionuclides such as Sr-89 and Sm-153 in hormone-resistant and chemotherapy-refractory metastatic prostate cancer. [ 8 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, during follow-up, two acute rapidly fatal myeloid leukemias and one chronic myeloid leukemia were observed. Hematological toxic effects are well known in patients treated with bone-targeting radionuclides [ 25 ]. Nevertheless, our data are in contrast with the long-term safety data of patients with prostate cancer treated with Radium-223 [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a significant fraction of the bone marrow is spared from irradiation. However, a recent meta-analysis of randomised controlled trials involving radionuclides concluded that there was no significant difference in haematological effects between 223 Ra and beta-emitting radionuclides, although it did confirm the advantage of 223 Ra with respect to overall survival and time to symptomatic skeletal events [46].…”
Section: Radium-223mentioning
confidence: 99%